BIMSTEC at a Crossroads: Enhancing Regional Cooperation through Institutionalization and Leadership - Lee , Hunjoo; Kim, Misu (Journal of Ecohumanism, 2024)
BIMSTEC (Bay of Bengal Initiative for Multi-Sectoral Technical and Economic Cooperation) represents a significant framework for regional cooperation, linking South Asia and Southeast Asia. Despite its potential, BIMSTEC has historically faced challenges in institutional development, struggling to distinguish itself from other regional organizations such as SAARC and ASEAN. However, recent geopolitical shifts and the stagnation of SAARC have positioned BIMSTEC as a more viable platform for regional integration. This study explores strategies to rejuvenate BIMSTEC by focusing on institutionalization and leadership dynamics, particularly in light of India’s growing influence within the organization. It examines how effective institutionalization can enhance BIMSTEC’s operational capacity, with particular emphasis on the role of formal and informal leadership. The study also analyzes the economic and political motivations of member states, highlighting the critical need for robust institutional frameworks to support sustainable cooperation. Through a comprehensive review of secondary data, including academic research and official documents, this paper provides policy recommendations for strengthening BIMSTEC’s role in regional cooperation.